2014
DOI: 10.1111/1541-4337.12107
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Control in Baker's Yeast Production: Mapping Patents

Abstract: During baker's yeast manufacturing, the fermentation process must be thoroughly controlled. This review of the patent literature provides new information on the early development of industrial fermentation processes. As shown by a review of 199 patents filed between 1900 and 2009, inventors in this field were mainly interested to improve yeast yields through the control of infection and sugar concentration in the growth media. Contrary to common belief, much attention was also given to continuous culture proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…For a few patents, this German inventor from Mannheim was linked to a German manufacturer, Norddeutsche Hefeindustrie AG, based in Berlin thus very far from his hometown. Stich also claimed 2 patents on mechanical foam control, described in this review, as well as 1 patent on molasses treatment, 1 on growth media (adjuncts), 1 on seeding conditions, and 2 on fermentation control with some link to aeration (Gélinas , ).…”
Section: Inventorsmentioning
confidence: 94%
See 4 more Smart Citations
“…For a few patents, this German inventor from Mannheim was linked to a German manufacturer, Norddeutsche Hefeindustrie AG, based in Berlin thus very far from his hometown. Stich also claimed 2 patents on mechanical foam control, described in this review, as well as 1 patent on molasses treatment, 1 on growth media (adjuncts), 1 on seeding conditions, and 2 on fermentation control with some link to aeration (Gélinas , ).…”
Section: Inventorsmentioning
confidence: 94%
“…Number of patent applications on media, fermentation control, and aeration and foam control during the production of baker's yeast according to filing date (5 y range). Data on media and fermentation control were obtained from Gélinas (, ). Since the publication of the latter reviews, the following 8 patents were found and counted above, specifically on growth media (YU 57002 filed in 2002; KR 100522264 filed in 2005; US 20120128853 filed in 2010; RU 2010152223 filed in 2010; CN 102311927 filed in 2011; RU 2012138881 filed in 2012; CN 104087521 filed in 2014), and fermentation control (RO 127019 filed in 2012).…”
Section: Evolution Of Patenting Activity According To Yearmentioning
confidence: 99%
See 3 more Smart Citations